2020
DOI: 10.1111/eva.13024
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent expression of cancer‐related genes in a long‐lived seabird

Abstract: Studies of model animals like mice and rats have led to great advances in our understanding of the process of tumorigenesis, but this line of study has less to offer for understanding the mechanisms of cancer resistance. Increasing the diversity of nonmodel species from the perspective of molecular mechanisms of natural cancer resistance can lead to new insights into the evolution of protective mechanisms against neoplastic processes and to a wider understanding of natural cancer defense mechanisms. Such knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The increased anthropogenic impacts on our environment is predicted to result in that the synergistic interaction between environmental stressors, parasites, telomere shortening and cancer development will be accelerated in the future (Giraudeau et al, 2018 , 2019 ; Greaves, 2015 ; Meitern et al, 2020 ; Monaghan, 2014 ; Sepp et al, 2019 ). For example, inverse associations have been observed in TL and air pollution (Zhao et al, 2018 ), traffic noise pollution (Dorado‐Correa et al, 2018 ) and chemical pollutants (Angelier et al, 2019 ; Blévin et al, 2016 ; Stauffer et al, 2017 ).…”
Section: A Life‐history Perspective: Individual Level Telomere—cancer...mentioning
confidence: 99%
See 1 more Smart Citation
“…The increased anthropogenic impacts on our environment is predicted to result in that the synergistic interaction between environmental stressors, parasites, telomere shortening and cancer development will be accelerated in the future (Giraudeau et al, 2018 , 2019 ; Greaves, 2015 ; Meitern et al, 2020 ; Monaghan, 2014 ; Sepp et al, 2019 ). For example, inverse associations have been observed in TL and air pollution (Zhao et al, 2018 ), traffic noise pollution (Dorado‐Correa et al, 2018 ) and chemical pollutants (Angelier et al, 2019 ; Blévin et al, 2016 ; Stauffer et al, 2017 ).…”
Section: A Life‐history Perspective: Individual Level Telomere—cancer...mentioning
confidence: 99%
“…To test if the assumption is correct, it would be crucial to get accurate estimates of cancer prevalence among for example, long‐lived sea birds. It is interesting to note that a recent study in common gulls reported a complex downregulation of the expression of eight cancer‐related genes with age, a process that might be interpreted as a mechanism suppressing cancer risk for five of the genes but as increasing the risk for the three other genes differently expressed between young and old gulls (Meitern et al, 2020 ). An important note is, when considering telomerase activity in long‐lived species and in association with cancer, that a detectable telomerase activity not necessarily result in telomere elongation as the enzyme has many other functions (e.g., inhibition of apoptosis in immune cells, enhancement of cellular inflammatory responses and maintenance of mitochondrial function, reviewed in Zheng et al, 2019 ).…”
Section: A Life‐history Perspective: Telomere and Cancer Dynamics Acr...mentioning
confidence: 99%
“…There is thus a need to explore, especially in long‐lived species, the evolution of protective mechanisms against neoplastic processes and natural cancer defense mechanisms in general. Meitern et al (2020, This volume) proposed that seabirds are promising model given their longevity and their habitats that are currently often polluted. This study revealed that old gulls differ from young ones both from the aspect of cancer susceptibility and of tumor suppression at the genetic level.…”
mentioning
confidence: 99%